The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Evaluating the relationship between spatial heterogeneity and temporal variability of larval fish assemblages in a coastal marine ecosystem (Haizhou Bay, China) - Zengguang Li; Zhenjiang Ye; Rong Wan; Yong Chen; Yongjun Tian; Yiping Ren; Hong Liu; Haisheng Hu; Robert Boenish (Marine Ecology, 2017)
In coastal marine ecosystems, spatial patterns of larval fish assemblages ( LFA s) tend to exhibit geographic stability because of relatively stable spawning site selection and predictable oceanographic phenomena such as eddies. To evaluate the relationship between spatial heterogeneity and temporal variability of LFA s, we conducted a high spatiotemporal resolution ichthyoplankton survey from April to July in 2013 in the shallow waters ( LFA s, likely owing to temperature effects of species composition and spawning period selection of adult fish, along with known temperature‐dependent survival rates of larval fish. Study of LFA spatiotemporal dynamics is essential for improved understanding of adult fish spawning behavior, and has potential to inform design and implementation of conservation and management measures (e.g. marine protected areas) in coastal systems.

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Study on the hydrodynamic characteristics of the rectangular V-type otter board using computational fluid dynamics - Qingchang Xu; Liuyi Huang; Fenfang Zhao; Xinxin Wang; Yanli Tang; Zhenlin Liang; Rong Wan; Peng Sun; Changdong Liu (Fisheries Science, 2017)

Use of random forests and support vector machines to improve annual egg production estimation - Zengguang Li; Rong Wan; Zhenjiang Ye; Yong Chen; Yiping Ren; Hong Liu; Yiqian Jiang (Fisheries Science, 2017)